GAYA HIDUP DALAM TEENLIT INDONESIA: KAJIAN SEMIOTIKA TERHADAP NOVEL MY FRIENDS MY DREAM KARYA KEN TERATE DAN GLAM GIRLS KARYA NINA ARDIANTI - Nurlailatul Qadriani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
Abstract: Teenlit as a part of popular literature is chosen for research with the aim of describing (1) picture of teen characters in Teenlit novels, (2) the forms of tenenage characters meaning in popular culture novels. Novels My Friends My Dream by Ken Terate published by Gramedia in 2005, Glam Girls by Nina Ardianti published by Gagas Media in 2008, are the objects of this study were analyzed by semiotic analysis method of Roland Barthes. This research showed that both of the novels also reveal show adolescents make sense of popular culture, through adolescence metropolitan lifestyle that characterized the consumption patterns of adolescents such as shopping at the mall, a teen trendsetters and have a career related to the popular world as social capital in their relationships. The pattern of consumption in adolescents experienced, indicate the change of lifestyle as a form of adaptation which is characterized by the appearance of a symbolic form of representing a popular teenager.